Respuesta :
- 3x-2y=-2--(1)
- 5x-3y=-4--(2)
- (1)×5 and (2)×3
[tex]\\ \tt\hookrightarrow 15x-10y=-10--(3)[/tex]
[tex]\\ \tt\hookrightarrow 15x-9y=-12--(4)[/tex]
Subtracting
[tex]\\ \tt\hookrightarrow -y=+2[/tex]
[tex]\\ \tt\hookrightarrow y=-2[/tex]
Put in eq(1)
[tex]\\ \tt\hookrightarrow 3x+4=-2[/tex]
[tex]\\ \tt\hookrightarrow x=-2[/tex]
Answer:
x = -2 and y = -2
Explanation:
Given equations:
3x - 2y = -2
5x - 3y = -4
---------------------
Make the value before y equal:
( 3x - 2y = -2 ) * 3
9x - 6y = -6 .........equation 1
( 5x - 3y = -4 ) * 2
10x - 6y = -8 ...........equation 2
solve them by elimination:
10x - 6y = -8
-9x + 6y = +6
----------------------
x = -2
If x is -2
Then y:
10x - 6y = -8 .................from equation 2
-6y = -8-10x
y = [-8 - 10(-2)]/-6
y = -2